Ijaz dan Ithnab dalam QS al-Baqarah: Sebuah Analisis Kritis tentang Efektivitas Bahasa Al-Qur'an dalam Mengkomunikasikan Pesan Ilahi - Dwi Ratnasari,; Dewi Nurjannah,; Mutmainnah Syam, (Journal of Arabic Education and Linguistics, 2025)
Al-ijaz and al-itnab are among the language styles found in the Qur'an al-Karim. This language style has a beautiful, special and distinct value equal to its position as the word of Allah SWT. This article aims to reveal the secrets behind these two language styles, focusing on surah Al-Baqarah. This study is a qualitative study that uses a descriptive and comparative approach. Based on sampling methods, this article selects 16 verses from surah Al Baqarah as samples to represent each language style discussed. Everything is explained with the aim of knowing the secrets and beauty of semantics. The research results found examples that contain very special semantics and goals, both implicit and explicit. Apart from that, it tries to make a deep impression on the human soul and heart. The secret to the beauty of the language contained in surah Al-Baqarah is: In terms of the style of the ijaz language, it contains verses that have a lot of meaning in a few pronunciations. And in terms of the style of ithnab, it contains verses that have little meaning in many pronunciations.